Inclusion of myxomycetes in the Red Data Book of Ukraine: feasibility, selection criteria and recommended species - Leontyev D.V.; Yatsiuk I.I.; Kochergina A.V. (Ukrainian Botanical Journal, 2020)
Myxomycetes is the only group of macroscopic terrestrial organisms not yet represented in the Red Data Book of Ukraine, although their need in conservation is recognized internationally. Myxomycetes are included in a number of Red Data Books and Red Lists of different regions of the world, including IUCN official publications; special reserves and international committees have been established to support their conservation. The state of knowledge about myxomycetes of Ukraine is now sufficient to determine a list of threatened species, which abundance can be monitored by conservationists. Currently, 301 species of myxomycetes have been registered in the country; among them, 202 species can be easily identified in the field without using special methods, and their records are confirmed by herbarium specimens with more or less exact geolocation data. For these species, distribution in Ukraine and in the world was determined and the Leroy's relative rarity weight was calculated. The species were subsequently divided into four categories, according to their relative rarity weight: A – rare in Ukraine and in the world (25 species), B – rare in Ukraine but common in the world (7), C – rare in the world but common in Ukraine (67), and D – common in Ukraine and in the world (103). Species assigned to the categories A–C are listed in the compiled Red List of myxomycetes of Ukraine. Furthermore, using additional criteria, seven species, selected from the category A, are recommended for inclusion in the Red Data Book of Ukraine: Diderma meyerae, Lamproderma pulveratum, L. spinulosporum, L. zonatum, Reticularia olivacea, Symphytocarpus trechispora, and Tubifera pseudomicrosperma. For these species, ecological and biogeographical characteristics and original illustrations are provided.